THE CORELATION OF PARENTAL COMMUNICATION BEHAVIOR TO SOCIAL MEDIA IN ADOLESCENTS IN CUKUH MUTUN HAMLET, SUAK VILLAGE RT01/RW03 SOUTH LAMPUNG - Uvilailati, Zalna; Meliyana, Ernauli; Ratnah, I (Jurnal Medicare, 2023)
As social beings, humans always carry out the process of communicating with one another intentionally or unintentionally. Communication has a very close relationship with social media because of social media, communication becomes faster and easier to do. Whether we realize it or not, the presence of new media, especially social media, has had a very big influence on human life, whether it is a good influence or a bad influence. The method used in this research is quantitative with a cross-sectional approach and purposive sampling. The population in this study were teenagers in Cukuh Mutun Hamlet Rt01/Rw03 Suak Village, South Lampung totaling 100 teenagers. With the results of the study obtained P of (0.000), so the conclusion is that there is a relationship between parental communication behavior on the use of social media in adolescents in Cukuh Mutun Hamlet Rt01/Rw03 Suak Village, South Lampung. Keywords: parental communication behavior, social media, adolescents